2021
DOI: 10.1007/s10911-021-09505-3
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Analyzing the Breast Cancer Lipidome and Its Relevance to Disease Progression and Treatment

Abstract: Abnormal lipid metabolism is common in breast cancer with the three main subtypes, hormone receptor (HR) positive, human epidermal growth factor 2 (HER2) positive, and triple negative, showing common and distinct lipid dependencies. A growing body of studies identify altered lipid metabolism as impacting breast cancer cell growth and survival, plasticity, drug resistance, and metastasis. Lipids are a class of nonpolar or polar (amphipathic) biomolecules that can be produced in cells via de novo synthesis or ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 161 publications
0
15
0
Order By: Relevance
“…Lipids are the main structural components of cell membrane compartment that also play a vital role as energy sources and signaling molecules. Dysregulated lipid metabolism pathways in breast cancer have received renewed interest, as oncogenic signaling and molecular heterogeneity regulate lipidomics and the progression of BC [ 17 ]. The key metabolic hallmarks of BC cells are alterations in fatty acid (FA) transport, uptake, de novo lipogenesis, storage and oxidation to generate ATP (adenosine triphosphate) ( Figure 2 ) [ 12 ].…”
Section: Plasticity Of Lipid Metabolismmentioning
confidence: 99%
“…Lipids are the main structural components of cell membrane compartment that also play a vital role as energy sources and signaling molecules. Dysregulated lipid metabolism pathways in breast cancer have received renewed interest, as oncogenic signaling and molecular heterogeneity regulate lipidomics and the progression of BC [ 17 ]. The key metabolic hallmarks of BC cells are alterations in fatty acid (FA) transport, uptake, de novo lipogenesis, storage and oxidation to generate ATP (adenosine triphosphate) ( Figure 2 ) [ 12 ].…”
Section: Plasticity Of Lipid Metabolismmentioning
confidence: 99%
“…As crucial biomolecules, lipids are not only the component of cell membranes but also signal transduction molecules and energy sources ( Bian et al, 2021 ; Ward et al, 2021 ; Batchuluun et al, 2022 ). An increasing number of studies have shown that lipid metabolism is abnormal in cancer ( Faubert et al, 2020 ; Snaebjornsson et al, 2020 ; Bian et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…What is noteworthy is that breast cancer is closely related to lipid metabolism. Breast cancer is mainly divided into hormone receptor (HR) positive subtype, human epidermal growth factor 2 (HER2) positive subtype, and triple-negative subtype, showing different degrees of lipid dependence ( Ward et al, 2021 ). It has been identified that APOL4, NR1H3, and other genes related to lipid metabolism are independent prognostic markers of breast neoplasm and can predict overall survival in breast cancer patients ( Chang and Xing, 2022 ; Wang and Wang, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations